Phytochemical Evaluation And Protective Effect Of Tithoniadiversifolia (Hemsl.) Leaf Extract Against Aspirin-Induced Ulcer In Wistar Rats (Journal of Namibian Studies : History Politics Culture, 2023)
Objectives: The objective of this study was to evaluate the phytochemical composition and gastroprotective properties of Tithonia diversifolia extract.Methods: Gas Chromatography-Mass Spectrophotometry (GC-MS) was used to quantify the chemical constituents present in the extract. Fourier Transform Infrared (FT-IR) spectroscopy was employed to identify functional groups in the extract. An acute toxicity study was conducted on rats to assess the safety of the extract. For the gastroprotective study, Wistar rats were divided into different groups and pretreated with different doses of T. diversifolia extract before ulcer induction with aspirin.Results: GC-MS analysis revealed the presence of twenty-eight chemical constituents in the extract,with benzyl alcohol, p-hydroxy-alpha-[(methylamino) methyl] being the most prominent. FT-IR analysis identified several functional groups in the extract. The acute toxicity study showed no signs of toxicity or mortality. Both the T. diversifolia extract and omeprazole (standard drug) significantly reduced ulcer parameters, antioxidant activity, phase II enzymes, matrix metalloproteinase activity, prostaglandin E2 levels, and inflammatory biomarkers compared to the negative control group. The percentage inhibition of ulcers followed a dose-dependent trend.Conclusions: The findings of this study suggest that the decoction of Tithonia diversifolia has potential gastroprotective properties against aspirin-induced ulcers. The extract exhibited significant reduction in ulcer parameters and modulation of various biochemical markers associated with ulcers. These results support the traditional use of T. diversifolia in ethnomedicine for the treatment of ulcers. Further studies are warranted to explore the specific mechanisms of action and potential clinical applications of T. diversifolia extract in gastroprotection.